Evaluation of the role of CDKN2B gene in type 2 diabetes mellitus and hypertension in ethnic Saudi Arabs - Maha Meshal AlRasheed (Elsevier, 2018)
Background: Coronary heart disease (CAD) is a multiple with several contributory risk traits, including type 2 diabetes and hypertension, which may share common genetic risk variants with the disease. Genome-wide association studies (GWASs) have yielded a wealth of information suggesting that CAD, the extent of contributory variants may differ according to genetic locus. The present study aimed at verifying whether the cyclin-dependent kinase 4 inhibitor B (CDKN2B) genomic region strongly associated with coronary artery disease (CAD)/myocardial infarction (MI) may also constitute risk for its risk factors type 2 diabetes mellitus (T2DM) and hypertension (HTN) in ethnic Saudi Arabs. Methodology: We genotyped eight CDKN2B SNPs for cardiovascular risk in a total of 4650 Saudi Arabs, (3049 male and 1601 female) by Taqman assay. Of these individuals, 3732 had primary hypertension and 2576 had type 2 diabetes mellitus. Results: Out of the eight studied SNPs, two, rs10757274_A [0.915 (0.840-1.00); p = 0.042], rs1333045_T [0.92(0.84-1.00); p = 0.048] were initially associated with type 2 diabetes but lost the association after multivariate adjustments for CAD, hypertension and MI, while rs10757274_A showed borderline association with hypertension. Conclusions: Our finding does not support the notion of a critical role for the CDKN2B gene locus as a HTN or T2DM cardiovascular risk in ethnic Arabs. The study also demonstrates the importance of replication studies in ascertaining the role of a genomic sequence in disease. Keywords: CDKN2B gene, Saudi Arab population, Association study, Type 2 diabetes mellitus, Hypertension